Implementing and testing branch-and-bound algorithm for the quadratic 0-1 problem on transputers - Schutz, G. (2013)
Discrete optimization problems are very difficult to solve, even if the dimention is small. For most of them the problem of finding an ε-approximate solution is already NP-hard. The branch-and-bound algorithms are the most used algorithms for solving exactly this sort of problems.